Malandragem à brasileira: o jeitinho brasileiro no road movie Bye Bye Brasil - Souza, Everton David Santos de (2018)
This study discusses the social, economic and cultural aspects of Brazil, highlighting the cinema as media stage through its representations. In route, through film analysis and narratological, we choose the film Bye Bye Brasil (Carlos Diegues, 1979), investigating an approach brazilian cinema, a cacth on road movie genre, as well as a historical contextualization of the period in which the film is portrayed. For that, an analysis was constructed in the observation of the representations of identity and nationality based on Hall (2006), as well as aspects of modernity according to Ortiz (1989), having as main aspect analyzed, the characteristics of malandragem and brazilian way, focused in the character Lorde Cigano and in your relationships with the other characters. In this sense, it was necessary to update the studies on “jeitinho brasileiro”, from DaMatta (1997), Barbosa (1992) and others.